The Influence of Physical Education on Self-Efficacy in Overweight Schoolgirls: A 12-Week Training Program - Latino, Francesca; Cataldi, Stefania; Bonavolontà, Valerio; Carvutto, Roberto; De Candia, Michele; Fischetti, Francesco (Frontiers in Psychology, 2021)
The purpose of this randomized controlled study was to investigate the impact of a 12-week Physical Education (PE) program on overweight schoolgirls' self-efficacy. We randomly assigned 60 overweight schoolgirls (15-17 years) to either an experimental moderate to vigorous aerobic exercises (̴ 90 min., three times a week) group (n = 30) or a control group (n = 30) that received non-specific regular physical education lessons with activities chosen by the curricular teacher mainly focused on team games and sports skills that aimed to achieve a general psycho-physical wellness (̴ 90 min., three times a week). In order to assess students' starting level and significant changes reached, at baseline and after training, a battery of standardized assessment motor tests, and a psychometric scale (Generalized self-efficacy scale - GES) were administered. At the end of the intervention, the experimental group reported considerable decrease in BMI, and a large improvement in self-efficacy (p < 0,001). No significant changes were found in the control group. The results suggested that 12-week moderate to vigorous aerobic exercises program is an effective weight loss intervention and a vehicle to promotes a range of outcomes important to adolescents' qualitative growth. Indeed, it could provide a positive and significant impact on overweight schoolgirls’ self-efficacy.